Spain : 2007 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
Spain's 2007 Article IV Consultation underlies that immediate growth prospects are bright and the central scenario is for a smooth landing but with appreciable downside risks. The Spanish economy enjoyed another year of remarkable growth in 2006, further extending its prolonged expansion. Output growth gathered pace in the course of 2006 to reach 3.9 percent for the year, and brisk job creation absorbed further increases in female participation and immigration, and inflation moderated appreciably.